Interactions of nitrogen and phosphorus cycling promote P acquisition and explain synergistic plant-growth responses - Schleuss, Per Marten; Widdig, Meike; Heintz-Buschart, Anna; Kirkman, Kevin; Spohn, Marie (Ecology (Durham), 2020)
Plant growth is often co-limited by nitrogen (N) and phosphorus (P). Plants might use one element to acquire another (i.e., trading N for P and P for N), which potentially explains synergistic growth responses to NP addition. We studied a 66-yr-old grassland experiment in South Africa that consists of four levels of N addition with and without P addition. We investigated the response of aboveground net primary production (ANPP) to N and P addition over the last 66 yr. Further, we tested whether phosphatase activity and plant P uptake depend on N availability, and vice versa, whether non-symbiotic N2 fixation and plant N uptake depend on P availability. We expected that the interaction of both elements promote processes of nutrient acquisition and contribute to synergistic plant growth effects in response to NP addition. We found synergistic N and P co-limitation of ANPP for the period from 1951 to 2017 but the response to N and P addition diminished over time. In 2017, aboveground P stocks, relative rRNA operon abundance of arbuscular mycorrhizal fungi, and soil organic P storage increased with N fertilization rate when N was added with P compared to the treatment in which only N was added. Further, N addition increased phosphatase activity, which indicates that plants used N to acquire P from organic sources. In contrast, aboveground N stocks and non-symbiotic N2 fixation did not change significantly due to P addition. Taken together, our results indicate that trading N for P likely contributes to synergistic plant-growth response. Plants used added N to mobilize and take up P from organic sources, inducing stronger recycling of P and making the plant community less sensitive to external nutrient inputs. The latter could explain why indications of synergistic co-limitation diminished over time, which is usually overlooked in short-term nutrient addition experiments.